Moderasi Beragama di Media Sosial: Narasi Inklusivisme dalam Dakwah - Wawaysadhya Wawaysadhya; Tri Utami Oktafiani; Pingki Laeli Diaz Olivia; Muhammad Baruzzaman (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2022)
This paper provides an explanation about the phenomena of religious moderation in social media. There is a tendency of new trend in religious phenomena amongst Indonesian millennial generation in this disruptive era. They are showing an interest on learn more about religion virtually. The easiness in accessing information is in a perfect proportion with the convenience of the information provider to share various kind of information, such as a religious content shared by ulama, or commonly known as dakwah. The approach of this paper is inclusivism theory on religious moderation. Religious moderation is considered as a relevant effort to cope with various kind of religious literacy on both sides, the preacher and the people, or internet user. The attempt on familiarization of the religious motion and naration can be done trough an inclusive dakwah. The result shows that there is a conceptional connection between virtual dakwah and religious moderation. There is also a diret connection between Virtual dakwah through social media and the spirit of inclusivism, that later become the main support of religious moderation. The attempt on familiarization of the religious motion and naration can also be done by religious figures and leaders with the messages of inclusivsm through virtual dakwah.